The Incidence of Intravascular Needle Entrance during Inferior Alveolar Nerve Block Injection - Taghavi Zenouz, Ali (Tabriz University of Medical Sciences, 2008)
BACKGROUND AND AIMS: Dentists administer thousands of local anesthetic injections every day. Injection to a highly vascular area such as pterygomandibular space during an inferior alveolar nerve block has a high risk of intravascular needle entrance. Accidental intravascular injection of local anesthetic agent with vasoconstrictor may result in cardiovascular and central nervous system toxicity, as well as tachycardia and hypertension. There are reports that indicate aspiration is not performed in every injection. The aim of the present study was to assess the incidence of intravascular needle entrance in inferior alveolar nerve block injections. MATERIALS AND METHODS: Three experienced oral and maxillofacial surgeons performed 359 inferior alveolar nerve block injections using direct or indirect techniques, and reported the results of aspiration. Aspirable syringes and 27 gauge long needles were used, and the method of aspiration was similar in all cases. Data were analyzed using t-test. RESULTS: 15.3% of inferior alveolar nerve block injections were aspiration positive. Intravascular needle entrance was seen in 14.2% of cases using direct and 23.3% of cases using indirect block injection techniques. Of all injections, 15.8% were intravascular on the right side and 14.8% were intravascular on the left. There were no statistically significant differences between direct or indirect block injection techniques (P = 0.127) and between right and left injection sites (P = 0.778). CONCLUSION: According to our findings, the incidence of intravascular needle entrance during inferior alveolar nerve block injection was relatively high. It seems that technique and maneuver of injection have no considerable effect in incidence of intravascular needle entrance.